Police officers' preferences for gender-based responding to domestic violence in China - Wang, Xiying (Journal of family violence, 2021)
This study examines Chinese police officers’ preferences for different formations of responders to domestic violence. Specifically, it assessed the connections between Chinese officers’ gender and gender-based attitudes and their perceptions of whether female officers, male officers, or mixed-gender officers are more suited for responding to battered women, offenders, and domestic violence overall. Survey data were collected from 1052 officers, including 278 females and 774 males from four provinces in China. Frequency distributions, cross-tabulations, and multivariate regression were used as data analysis methods. Chinese officers, in general, were more likely to believe that female officers are more suited to work with battered women, the male officer is more apt to handle offenders, and a combination of male and female officers are more adapted to deal with “domestic violence overall”. Female officers preferred male officers over themselves in investigating “domestic violence overall.” Officers who have more support for gender equality or more tolerance for domestic violence are more likely to believe that, compared to male officers, female officers are more suitable to work with batter women, and a combination of male and female officers is better to provide service to battered women and to respond to “domestic violence overall.” Policymakers and police administrators should strive to promote the value of a more gender-balanced police force and involve more female officers to work in responding to domestic violence.